Long-Term Empirical Studies Highlight Multiple Drivers of Temporal Change in Bird Fauna in the Wet Forests of Victoria, South-Eastern Australia - Lindenmayer, David; Bowd, Elle; McBurney, Lachlan (Frontiers in Ecology and Evolution, 2021)
Birds are high profile elements of the vertebrate biota in almost all terrestrial ecosystems worldwide. Many studies have uncovered evidence of a decline in bird biodiversity, but temporal patterns of change vary among ecosystems and among bird species with different life history traits. Ecosystem-specific, long-term studies are critical for identifying patterns of temporal change in bird biodiversity and the drivers of that change. Here we present a case study of drivers of temporal change in the bird fauna of the Mountain Ash and Alpine Ash eucalypt forests of south-eastern Australia. Using insights from observational studies and experiments conducted over the past 18 years, we discuss the direct and interactive effects of fire and logging on birds. The extent and severity of wildfires have major negative effects on almost all bird species, and have persisted for more than a decade after the last major conflagration (in 2009). Logging has markedly different effects on birds than those quantified for fire, and may have resulted in elevated levels of site occupancy in remaining uncut areas in the landscape. Both fire and logging have led to marked losses in the extent of old growth forest in Mountain Ash and Alpine Ash ecosystems. This is a concern given the strong association of most species of birds with old forest relative to younger age cohorts. Based on an understanding of the effects of fire and logging as drivers of change, we propose a series of inter-related management actions designed to enhance the conservation of avifauna in Mountain Ash and Alpine Ash ecosystems. A particular focus of management must be on increasing the interval between fires and limiting the spatial extent of wildfires and, in turn, significantly expanding the extent of old growth forest. This is because old growth forest is where most bird species are most likely to occur, and in the event of future wildfires, where fire severity will be lowest. Expansion of the old growth estate will require commercial logging operations to be excluded from large parts of Mountain Ash and Alpine Ash forests.